Asuhan Keperawatan Nyeri Akut Pada Tn. E Dengan Gout Arthritis Dan Penerapan Kompres Hangat Jahe Merah Di Rumah Bahagia Embung Fatimah Dinas Sosial Kota Tanjungpinang - Eka Afriani; Syamilatul Khariroh; Mawar Eka Putri; Zuraidah Zuraidah (Excellent Health Journal, 2025)
The occurrence of gouty arthritis in the joints can be very disruptive to daily activities. These effects include severe joint pain/ache, inflammation, redness, and a warm sensation in the affected area. In addition, gouty arthritis can also cause long-term complications such as joint damage, tophi (lumps of uric acid crystals under the skin), kidney stones, and even kidney failure if left untreated. To overcome the problem of pain can be done pharmacologically and non-pharmacologically. Non-pharmacologically, namely with warm compresses of red ginger. This scientific work aims to provide comprehensive nursing care to clients with acute pain disorders and the application of warm red ginger compresses. This research uses descriptive observational methods in the form of case studies. The subject in this case is Mr. E who is 72 years old with Gout Arthritis at Rumah Bahagia Embung Fatimah Social Service of Tanjungpinang City. Data were obtained from interviews, observations, physical examinations, supporting examinations, and documentation studies. The implementation of nursing care was carried out for 3 weeks from December 31, 2024 - January 17, 2025. The results of nursing care decreased pain intensity using pain scale measurements (Visual Analog Scale). After 3 weeks of nursing action the client's pain scale was at score 0 (no pain). It is hoped that the results of this scientific work will become additional knowledge for health services and the Rumah Bahagia Embung Fatimah in dealing with acute pain disorders by applying warm compresses of red ginger so as to improve health services to clients.